PENGARUH STRATEGI GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK TUPPERWARE DI KOTA JAMBI - Sinaga, Herlina (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2015)
The purpose of this study was to explain the effect of the Green Marketing strategy on the purchasing decision of Tupperware products and to analyze the effect of the Green Marketing strategy on the purchasing decision of Tupperware products. The analytical method used in this study is a descriptive method and a quantitative method using the SPSS tool to test multiple linear regression. The results of the study concluded that simultaneously showing that the green marketing strategy with the attributes of green input, green process, green output, and green value has an influence on purchasing decisions by 31.369%. Thus Tupperware products are considered capable of explaining to consumers in deciding to purchase Tupperware products. In partial testing: shows that Green Input has no influence on purchasing decisions. There is no significant effect of green input on purchasing decisions, this is because green input is still considered to have little influence on purchasing decisions, but green input is still in the good category by consumers in deciding to purchase Tupperware products in Jambi City. In partial testing: shows that green process, green output, and green value have an influence on purchasing decisions for Tupperware products. There is a significant influence of green process, green output, and green value on purchasing decisions because green process, green output, and green value with the indicators presented are considered influential to consumers so that they can influence purchasing decisions for Tupperware products.